Detection of Mycobacterium tuberculosis complex DNA in oronasal swabs from infected African buffaloes (Syncerus caffer) - Charlene Clarke; David V. Cooper; Michele A. Miller; Wynand J. Goosen (Scientific Reports, 2022)
Abstract Mycobacterium bovis (M. bovis), a member of the Mycobacterium tuberculosis complex (MTBC), is the causative agent of bovine TB (bTB) in animals. Spread occurs through inhalation or ingestion of bacilli transmitted from infected individuals. Early and accurate detection of infected African buffaloes shedding M. bovis is essential for interrupting transmission. In this pilot study, we determined if MTBC DNA could be detected in M. bovis infected buffalo oronasal secretions using a molecular transport media (PrimeStore MTM) with oronasal swabs and a rapid qPCR assay (Xpert MTB/RIF Ultra). Bovine TB test-positive buffaloes were culled, then tissue samples and oronasal swabs collected post-mortem for mycobacterial culture and Ultra testing, respectively. The Ultra detected MTBC DNA in 5/12 swabs from M. bovis culture-confirmed buffaloes. Oronasal swabs from M. bovis negative buffaloes (n = 20) were negative on Ultra, indicating the high specificity of this test. This study showed that MTM can successfully preserve MTBC DNA in oronasal swabs. The proportion of MTBC positive oronasal swabs was higher than expected and suggests that the Ultra may be an additional method for identifying infected buffaloes. Further studies are needed to confirm the utility of the Ultra assay with oronasal swabs as an assay to evaluate possible MTBC shedding in buffaloes.